İdarenin sağlık turizmine ilişkin faaliyetleri - Arın, Uğur (My University, 2025)
İdarenin sağlık turizmine ilişkin faaliyetleri Bu tez, sağlık turizmi alanında idarenin faaliyetlerini ele almaktadır. Tezin ilk bölümünde sağlık turizmi kavramı detaylı biçimde açıklanmakta; medikal, termal, wellness, yaşlı ve engelli sağlık turizmi gibi alt başlıklar üzerinden sağlık turizminin kavramsal kapsamı ortaya konmaktadır. İlk bölümün ikinci kısmında sağlık turizmi hukukunun normatif dayanakları incelenmiştir ve ardından sağlık turizm özneleri açıklanmıştır. Tezin ikinci bölümünde idarenin sağlık turizmiyle ilgili faaliyetleri irdelenmektedir. Bu kısımda idarenin bu alanda gerçekleştirdiği öngörme, özendirme ve destekleme, kamu hizmeti ve kolluk faaliyetleri mevzuat çerçevesinde irdelenmiştir. Üçüncü bölümde ise karşılaşılan uygulama sorunları değerlendirilmiş ve bazı ülke örnekleri ile analiz yapılmıştır. Çalışma, sağlık turizminin yalnızca ekonomik değil aynı zamanda insan sağlığı ve kamu hizmeti açısından önemli bir alan olduğunu vurgulamakta ve idarenin daha etkin, şeffaf ve kapsayıcı politikalar üretmesinin gerekliliğini ortaya koymaktadır.

Public administration’s activities related to health tourism This thesis addresses the activities of the administration in the field of health tourism. In the first chapter, the concept of health tourism is explained in detail; through subheadings such as medical, thermal, wellness, elderly and disabled health tourism, the conceptual scope of health tourism is presented. In the second part of the first chapter, the normative bases of health tourism law are examined, and then the subjects of health tourism are explained. The second section of the thesis examines the activities of the administration related to health tourism. In this section, the administration's planning, promotion and support, public service and law enforcement activities in this field are examined within the framework of the legislation. In the third section, the implementation problems encountered are evaluated and analyzed with examples from other countries. The study emphasizes that health tourism is not only an economic field but also an important field in terms of human health and public service, and reveals the necessity for the administration to produce more effective, transparent and inclusive policies.
Public administration’s activities related to health tourism
Keywords: Health aspects; Health resorts; International health tourist; İdarenin faaliyetleri; Medical tourism; Medikal turizm; Public administration; Sağlık merkezleri; Sağlık turizmi; Sağlık yönleri; Tourism; Turizm; Turkey; Türkiye; Uluslararası sağlık turisti Health tourism